KOMBINASI KOMPRES AIR HANGAT DAN MINUMAN JAHE TERHADAP PENURUNAN NYERI PUNGGGUNG PADA IBU HAMIL TRIMESTER II DAN III - Meda Yuliani; Linda Rofiasari; Dias Sri Lestari (Sekolah Tinggi Pariwisata Mataram, 2023)
Back pain in pregnancy is the result of anatomical, physiological, and hormonal changes. As many as 70% of pregnant women in the second and third trimesters experience back pain. Warm water compresses and ginger drink are non-pharmacological methods that can reduce back pain. The purpose of this study was to determine the effect of giving a combination of warm water compresses and ginger drinks to reduce back pain in pregnant women. The method used by the researcher is Quasy Experiment with one group pretest-posttest. The number of samples used in this study were 30 people using purposive sampling technique. The results showed as many as 20 mothers experienced moderate pain before the intervention. After the intervention, 21 mothers experienced mild pain. Based on the Wilcoxon test, there is a p-value of 0.000 <0.05, meaning that there is an effect of giving a combination of warm water compresses and ginger drink to reduce back pain in pregnant women